Aphids (Hemiptera: Aphidoidea) of ornamental plants from Sao Carlos, Sao Paulo state, Brazil - Peronti, A.L.B.G.=700 1 Sousa Silva, C.R.
(Es, En)
ilus., 33 ref.
Keywords: RECOLECCION; APHIDOIDEA; HEMIPTERA; INSECTA; PLANTAS ORNAMENTALES; INSECTOS DAÑINOS; BRASIL